2023
DOI: 10.31849/elsya.v5i1.6773
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Grammarly towards Indonesian EFL Students’ First-Degree Thesis Writing Confidence

Abstract: Students completing their studies in the English Education Study Program must be required by thesis writing and submission. It was also acknowledged that the supervisors had afforded proper supervision. Nevertheless, for the English structure of the thesis writing correctness, it still needed help from an application, Grammarly. Therefore, this research aimed to describe the research participant’s engagement and how the application has influenced confidence in writing a thesis, and the confidence is exposed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although Hicham and Bachir (2020) present a noteworthy proposition, it is crucial to recognize that the process of rectifying grammatical faults in written compositions has been significantly easier with technological improvements. Even, the technological application has successfully built students' confidence in being free from grammatical mistakes (Setyani et al, 2023;Ayu & Nurweni, 2023). "Automated Writing Evaluation (AWE) software is widely employed in the enhancement of writing proficiency among second language (L2) learners.…”
Section: Suryanto Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Although Hicham and Bachir (2020) present a noteworthy proposition, it is crucial to recognize that the process of rectifying grammatical faults in written compositions has been significantly easier with technological improvements. Even, the technological application has successfully built students' confidence in being free from grammatical mistakes (Setyani et al, 2023;Ayu & Nurweni, 2023). "Automated Writing Evaluation (AWE) software is widely employed in the enhancement of writing proficiency among second language (L2) learners.…”
Section: Suryanto Et Almentioning
confidence: 99%
“…The extensive use of Grammarly demonstrates an acknowledgment of its efficacy in improving writing skills throughout many educational settings. Multiple research studies have shown that using Grammarly has yielded a substantial enhancement in students' writing confidence (Setyani et al, 2023). Enhancing confidence is a crucial element in the learning…”
Section: A Introductionmentioning
confidence: 99%